Occurrence of Salmonella sp. and coagulase-positive staphylococci in raw eggs and Coalho cheese: comparative study between two cities of Brazil’s northeast - Evêncio-Luz, L (Sociedade Brasileira de Microbiologia, 2012)
Microbiological analyses of chicken eggs in Recife and Salvador have shown a high occurrence of Salmonella in the egg shells and yolks. Likewise, the occurrence of Salmonella plus coagulase-positive staphylococci in Coalho cheese reached alarming levels. The data revealed a significant risk of infections and intoxications from consuming these foods in the cities.